Behavior and Regional Cortical BOLD Signal Fluctuations Are Altered in Adult Rabbits After Neonatal Volatile Anesthetic Exposure - Drobyshevsky, Alexander; Miller, Mike J.; Li, Limin; Dixon, Conor J.; Venkatasubramanian, Palamadai N.; Wyrwicz, Alice M.; Aksenov, Daniil P. (Frontiers in Neuroscience, 2020)
Neonatal and infant exposure to volatile anesthetics has been associated with long-term learning, memory and behavioral deficits. Although early anesthesia exposure has been linked to a number of underlying structural abnormalities, functional changes associated with these impairments remain poorly understood. To investigate the relationship between functional alteration in neuronal circuits and learning deficiency, resting state functional MRI connectivity was examined in adolescent rabbits exposed to general anesthesia as neonates (1 MAC isoflurane for 2 hours on postnatal days P8, P11 and P14) and unanesthetized controls, before and after training with a trace classical eyeblink conditioning (ECC) paradigm. Long-range connectivity was measured between several key ROIs, including primary and secondary somatosensory cortex, thalamus, hippocampus and cingulate. In addition, metrics of regional BOLD fluctuations amplitudes and coherence, Amplitude of Low Frequency Fluctuations (ALFF), fractional ALFF and Regional Coherence (ReHo) were calculated. Our results showed that the trace ECC learning rate was significantly lower in the anesthesia-exposed group. No anesthesia-related changes in long-range connectivity, fALFF or ReHo were found between any ROIs. However, ALFF was significantly higher in anesthesia-exposed rabbits in primary and secondary somatosensory cortices, and ALFF in those areas was a significant predictor of the learning performance for trace ECC. The absence of anesthesia-related changes in long range thalamocortical connectivity indicates that functional thalamocortical input is not affected. Higher ALFF in somatosensory cortex may indicate developmental disruption of cortical neuronal circuits after neonatal anesthesia exposure, including excessive neuronal synchronization that may underlie observed cognitive deficits.